2023
DOI: 10.3390/pathogens12030410
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Clinical Acinetobacter baumannii Isolate to Hospital Environment during the COVID-19 Pandemic

Abstract: The aim of this study was to find the source of Acinetobacter baumannii in the intensive care unit (ICU) after an outbreak during the coronavirus disease 2019 (COVID-19) pandemic, as there was no A. baumannii detected on usually screened susceptible surfaces. The screening of the ICU environment was done in April 2021 when eleven different samples were taken. One A. baumannii isolate was recovered from the air conditioner and was compared with four clinical A. baumannii isolates obtained from patients hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A. baumannii exhibits an outstanding tendency to cause hospital outbreaks [ 15 , 16 ], which became an additional problem during the COVID-19 pandemic [ 17 ]. One of the reasons for this lies in its exceptional ability to survive for up to 60 days on various surfaces, including human skin and dry inanimate materials such as filter paper, glass, cotton, and metal, as well as on hospital surfaces [ 18 , 19 ], which underlies the necessity for accurate and reliable isolate typing in order to discriminate outbreak-causing strains. In general, typing techniques can be divided into phenotypic-based methods, DNA banding pattern-based methods, partial sequence-based methods, and whole genome sequencing (WGS)-based methods [ 16 ].…”
Section: Isolate Typing Methods For a Baumanniimentioning
confidence: 99%
See 1 more Smart Citation
“…A. baumannii exhibits an outstanding tendency to cause hospital outbreaks [ 15 , 16 ], which became an additional problem during the COVID-19 pandemic [ 17 ]. One of the reasons for this lies in its exceptional ability to survive for up to 60 days on various surfaces, including human skin and dry inanimate materials such as filter paper, glass, cotton, and metal, as well as on hospital surfaces [ 18 , 19 ], which underlies the necessity for accurate and reliable isolate typing in order to discriminate outbreak-causing strains. In general, typing techniques can be divided into phenotypic-based methods, DNA banding pattern-based methods, partial sequence-based methods, and whole genome sequencing (WGS)-based methods [ 16 ].…”
Section: Isolate Typing Methods For a Baumanniimentioning
confidence: 99%
“…Members of the three major ‘European’ lineages are associated with the majority of hospital outbreaks caused by A. baumannii worldwide and a higher percentage of resistance to many antimicrobial drugs [ 17 , 19 , 80 , 81 ]. IC2 isolates frequently showed higher resistance rates to all antimicrobial agents than the other genotypes [ 82 ].…”
Section: Current Situation and Historical Spread Of Ic1-ic9 Worldwidementioning
confidence: 99%
“…The second, on the other hand, suggests that lipid A is present, but in a form altered by mutation of the pmrA and/or pmrB gene, which affects the lowering of colistin's affinity for LPS [47]. Increasingly, clinicians are also encountering multidrug-resistant strains, which is probably due to prior antibiotic therapy, very often inappropriately administered [48]. It is believed that for infections caused by A. baumannii, monotherapy should not be used, but rather a combination of compounds that would condition protection against the development of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection with A. baumannii MDR significantly increases morbidity and mortality, especially in COVID-19 patients in intensive care [ 72 ]. In addition, this bacterium has been implicated in several outbreaks in healthcare facilities [ 23 , 73 ]. Inappropriate use of personal protective equipment, poor adherence to hand hygiene protocols, and irresponsible use of antibiotics are among the main factors contributing to the outbreak of this nosocomial MDR organism [ 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this bacterium has been implicated in several outbreaks in healthcare facilities [ 23 , 73 ]. Inappropriate use of personal protective equipment, poor adherence to hand hygiene protocols, and irresponsible use of antibiotics are among the main factors contributing to the outbreak of this nosocomial MDR organism [ 73 ]. As with K. pneumoniae , several studies worldwide have reported that A. baumannii strains with complete resistance to all tested antibiotics except colistin are increasingly being isolated from blood samples collected from ICU patients [ 8 , 71 ].…”
Section: Introductionmentioning
confidence: 99%